PENYELESAIAN KREDIT MACET PADA LEASING TERHADAP MOTOR YANG DI BEBANI JAMINAN FIDUSIA - SINAGA, MIKI TYSON (Journal of Law ( Jurnal Ilmu Hukum ), 2018)
ABSTRACTIn the sense of fiduciary cum creditore, a creditor holding a collateral object cannot act like an owner of the object. The debtor believes that the creditor will not have collateral forever and will fulfill his promise to return the collateral if the debtor has fulfilled his obligations. The purpose of this study is (1). To find out the implementation of a credit agreement with fiduciary collateral for motor vehicles, (2). To find out the legal consequences for debtors providing fiduciary mortgages for motorized vehicles that are pledged with fiduciary guarantees to third parties.This study uses an empirical juridical method approach with research subjects credit agreement with fiduciary collateral for mortgaged vehicles.To a third party at Adira Finance Samarinda. While the object of research is Adira Finance Samarinda. Data were collected using credit agreement instruments, interviews and documentation.The results of the study show that: (1) The process and mechanism of the loan agreement to be a fiduciary guarantee in practice are as follows: (a) Adira FinanceSamarinda accepts collateral in the form of BPKB vehicles, letters / invoices / lists of machines and invoices (based on contracts, SPK, etc.) that can generate receivables from bills) (b) The notary makes a Fiduciary Deed of guaranteed items This is based on the deed of Credit Agreement made between the debtor and Adira Finance Samarinda. (c) With respect to the fiduciary deed, the Notary shall register at the Fiduciary Registration Office for the issuance of a fiduciary guarantee certificate for Adira Finance Samarinda as the creditor of preference. (2) In the event of a bad credit, the settlement will also differ between those registered or not registered with the KPF. For fiduciary guarantees that are not registered, the creditor cannot use the execution title that is normally enjoyed by the fiduciary creditor. The creditor can only file a civil suit against the debtor. Execution of the executable title stated in Article 29 of the UUF is as follows: 1) If the debtor or fiduciary breeder fails, the execution of the object which is the object of fiduciary security can be made by: a) Execution of the executable title as referred to in Article 15 paragraph (2) by fiduciary recipients; b) The sale of objects which become the object of fiduciary security over the power of the recipient of the fiduciary himself through public auctions and take the payment of the receivables from the proceeds of the sale; c) Sales are carried out based on the agreement of the fiduciary giver and fiduciary recipient, then the highest price will be beneficial to the parties. 2) The sale is made after one month has passed when written in writing by the fiduciary recipient to the parties concerned and announced in at least two newspapers circulating in the area concerned.Â KeywordsÂ  : Bad Credit, Motorcycle Leasing, Fiduciary Guarantee